Planting date of peas Pisum sativum for seed production in Central Brazil - Galrão, Enéas Zaborowsky; Vargas, Milton Alexandre T.; Lobato, Edson; Oliveira, Heitor A. de (Pesquisa Agropecuaria Brasileira, 2014)
A date of planting experiment using peas was conducted in Central Brazil on a Red Dark Latosol Soil. An American variety, Resistant Early Perfection 326, and a variety from Morocco, Roi des Fins Verts, were planted on five different planting dates. The best planting date was between April 1st and May 10th. Both varieties showed high yields at all planting dates. Yields varied from 2,187 to 3,434 kg/ha, as compared with Rio Grande do Sul yields, which did not exceed 1,800 kg/ha. These results indicated great agricultural potential for pea seed production in this area. Seed production is considered one of the most limiting factors for this crop in Brazil.